2018
DOI: 10.1136/bcr-2018-226598
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial anaerobic infection with a deep abscess in the supraspinous fossa following a subacromial corticosteroid injection

Abstract: In September 2015, a male aged 61 years with poorly controlled diabetes (his only medical problem) had left shoulder surgery that included an arthroscopic acromioplasty with debridement of suture material from a rotator cuff repair done 10 years prior. A subacromial corticosteroid injection was given 7 months later for pain and reduced motion. Three weeks later a fulminate infection was evident. Cultures grew Propionibacterium acnes. Treatment included two arthroscopic debridement surgeries and 8 weeks of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The close proximity (five weeks) of our patient’s subacromial corticosteroid injection to his open RCR may have increased the risk of postoperative infection. This supposition is based on anecdotal and retrospective observations [ 7 , 37 ]. However, a study of 12,060 patients who had a shoulder corticosteroid injection within one year of arthroscopic RCR on the same shoulder found that the risk of infection was significantly increased only when the injection is given within one month of the surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The close proximity (five weeks) of our patient’s subacromial corticosteroid injection to his open RCR may have increased the risk of postoperative infection. This supposition is based on anecdotal and retrospective observations [ 7 , 37 ]. However, a study of 12,060 patients who had a shoulder corticosteroid injection within one year of arthroscopic RCR on the same shoulder found that the risk of infection was significantly increased only when the injection is given within one month of the surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly isolated pathogen from abscesses is Staphylococcus aureus , as was the case in both of our patients. There are several hypothesised aetiologies that can result in abscess formation; the causative organisms may enter the tissue by direct implantation (e.g., a penetrating injury with a contaminated object) [ 6 ] or secondary to trauma [ 2 , 7 ]. They may also enter tissue by direct migration from a location where there is resident flora into an adjacent, normally sterile area because natural barriers have been disrupted (e.g., an area of cellulitis).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible devastating complication of the corticosteroid injection is subsequent infection. There have been several case reports regarding the infection risk following the corticosteroid injection [12, 27, 29]. Armstrong and Dias [1] reported a correlation between intraoperative intra‐articular corticosteroid injection and onset of septic arthritis following arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 99%